Inequity and Exclusion in the Delivery of Health Services in Maseru,Lesotho - Thoahlane, Malesia Sylviah (My University, 2018)
For Centuries, health sectors have embarked on a journey to provide equitable and inclusive health services for all but it has been a major challenge. This is the case in Lesotho, the Ministry of Health has made it its priority to ensure the provision of equitable health services for all but, there are disparities observed. Consequently, this study explored the factors behind the problem of inequity and exclusion in the delivery of health services in Maseru, the governance trends and strategies in the Ministry of Health and their implications for equity and inclusiveness particularly with respect to access to health services. The research study was conducted using qualitative approach and data collected through interviews to probe among the participants the factors behind the inequity and exclusion that exist. Secondary data in the form of the Ministerial Strategic Development Plans and Budget allocations were also analysed in the research to mainly identify the trends and strategies in the Ministry. The main purpose of the research was to establish the factors behind the inequity and exclusion problems, identify possible solutions and make recommendations. The findings suggest a number of factors behind the problem of inequity and exclusion in the delivery of health services in Maseru. Included is lack of financial resources leading to multiple other factors such as poor infrastructure, limited human resources and failure by the Ministry to fully decentralize. Further, identified is the relationship between the factors thus we can conclude that one factor is as a result of another and visa-versa. Possible solutions to be the problem are provided and so are recommendations made.
Submitted in partial fulfilment of the degree of Masters of Management (In the field of Public Policy) School of Governance University of the Witwatersrand March 2018
Keywords: Health services accessibility--Lesotho; Right to health--Lesotho